MU-MIMO Performance with a Circular Base Station Array and Semi-Orthogonal User Selection - Cantoni, A.; Li, Bin; Dam, Hai Huyen Heidi (2015)
The paper presents results of an investigation of a MU-MIMO system suitable for providing broadband services. The base station has a circular array and each user has a single high gain antenna. Two optimum zero forcing beamformers are considered and semi-orthogonal user selection is used to schedule users in the downlink. A key point of the investigation is to determine the maximum number of users that can be scheduled for simultaneous transmission in order to achieve high spectral efficiency and still maintain acceptable performance in terms of sum rate and also all user rates.